EFFECTS OF INCOME, EDUCATION AND NUMBER OF FAMILY MEMBERS TOWARDS THE DEVELOPMENT OF CHILD WORKER IN BIREUEN DISTRICT - Cut Nurul Hikmah; Hijri Juliansyah (LPPM Universitas Malikussaleh, 2019)
This study aims to analyze of effect of income, education and the number of family members on the development of child labour in Bireuen Regency. The data in this study are obtained by distributing questionnaires to 69 respondents who are child workers in Bireuen Regency. The sampling technique used is Random Sampling and the data are analyzed by using Multiple linear regression. The results of the study indicated that the Head of household income and education have a significant and negative effect on the development child workers in Bireuen Regency, The number of family members has a positive and significant effect. Simultaneously, the income and education of the Head of household and the number of family members significantly affect the development of child workers in Bireuen Regency.